2012
DOI: 10.1021/ja211876p
|View full text |Cite
|
Sign up to set email alerts
|

The Substrate-Bound Crystal Structure of a Baeyer–Villiger Monooxygenase Exhibits a Criegee-like Conformation

Abstract: The Baeyer–Villiger monooxygenases (BVMOs) are a family of bacterial flavoproteins that catalyze the synthetically useful Baeyer–Villiger oxidation reaction. This involves the conversion of ketones into esters or cyclic ketones into lactones by introducing an oxygen atom adjacent to the carbonyl group. The BVMOs offer exquisite regio- and enantiospecificity while acting on a wide range of substrates. They use only NADPH and oxygen as cosubstrates, and produce only NADP+ and water as byproducts, making them env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 46 publications
2
100
0
Order By: Relevance
“…It has been previously noted that the CHMO Rotated structure, which is in an ideal position for formation of the Criegee intermediate, does not place cyclohexanone close to these residues. 28 In contrast, both CHMO Tight and CHMO Loose place ε-caprolactone in close proximity to these key residues (Figure 3). Assuming that the substrate, in the presence of the peroxyanion intermediate, would also bind in the same manner as the product in our structures, this strongly suggests that the acceptance of substrates, as well as the regio-and enantiospecificity of the enzyme, is determined in the Loose and/or Tight conformations.…”
Section: Results Crystal Structures Of Chmo In Complex With Itsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously noted that the CHMO Rotated structure, which is in an ideal position for formation of the Criegee intermediate, does not place cyclohexanone close to these residues. 28 In contrast, both CHMO Tight and CHMO Loose place ε-caprolactone in close proximity to these key residues (Figure 3). Assuming that the substrate, in the presence of the peroxyanion intermediate, would also bind in the same manner as the product in our structures, this strongly suggests that the acceptance of substrates, as well as the regio-and enantiospecificity of the enzyme, is determined in the Loose and/or Tight conformations.…”
Section: Results Crystal Structures Of Chmo In Complex With Itsmentioning
confidence: 99%
“…Combining the new CHMO Tight and CHMO Loose crystal structures with the previously reported CHMO Rotated structure, we now have a crystal structure with either substrate or product bound for each of the six critical substrate-and product-bound states proposed in the BVMO structural mechanism. 28 These are also all structures of the same enzyme, allowing them to be compared directly. The CHMO Rotated crystal structure corresponds to the Criegee-like states (states F and G), which are characterized by a closed off binding pocket that is large enough to accommodate a wide range of larger substrates.…”
Section: Results Crystal Structures Of Chmo In Complex With Itsmentioning
confidence: 99%
“…The crystal structure of CHMO was reported several years ago and this highlighted multiple conformations of the bound nicotinamide coenzyme required to reduce the flavin and stabilize formation of the Criegee intermediate formed in the reaction cycle [30]. More recent studies have reported the structure of a CHMO complex with NADP + and 2-cyclohexenone and reveal major rotation of the NADP + cofactor away from the flavin cofactor so that it is no longer stacked with the tricyclic isoalloxazine ring [31]. In this new conformation, cyclohexanone is now located over the flavin in a position that enables formation of the Criegee intermediate.…”
Section: Catalytic Cycles and New Chemistriesmentioning
confidence: 94%
“…Previous structural as well as mutagenesis studies have concluded that the C4a-(hydro)peroxyflavin intermediate is stabilized by NADP + which remains bound until the last step of the catalytic cycle [8,[29][30][31][32]. However, if this intermediate is not stabilized or the NADP + binding is compromised, the uncoupling of the enzyme results in hydrogen peroxide release.…”
Section: Measurement Of the C4a-(hydro)peroxyflavin Intermediatementioning
confidence: 99%